2013
DOI: 10.1152/physrev.00017.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Adipose Tissue Function and Dysfunction in Obesity

Abstract: The rise in the incidence of obesity has led to a major interest in the biology of white adipose tissue. The tissue is a major endocrine and signaling organ, with adipocytes, the characteristic cell type, secreting a multiplicity of protein factors, the adipokines. Increases in the secretion of a number of adipokines occur in obesity, underpinning inflammation in white adipose tissue and the development of obesity-associated diseases. There is substantial evidence, particularly from animal studies, that hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
551
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 707 publications
(599 citation statements)
references
References 232 publications
(375 reference statements)
24
551
2
22
Order By: Relevance
“…White adipose tissue is a major endocrine and secretory organ, with white adipocytes releasing a multiplicity of factors in the form of diverse adipokines, as well as fatty acids and other lipid moieties (Frühbeck et al, 2001;Trayhurn & Beattie, 2001;Rajala et al, 2003;Trayhurn, 2013). A number of adipokines are associated with the immune system and inflammation, and the expression and secretion of some of these protein signals and factors rise in obesity (Rajala et al, 2003;Hotamisligil, 2006;Trayhurn, 2013); examples include TNFα (tumour necrosis factor α), IL-6 (interleukin-6) and leptin. A notable exception is the hormone adiponectin, with its anti-inflammatory and insulin sensitising actions (Ouchi et al, 1999;Yokota et al, 2000;Berg et al, 2001;Yamauchi et al, 2001), the production and secretion of which falls as fat mass expands (Arita et al, 1999;Hotta et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…White adipose tissue is a major endocrine and secretory organ, with white adipocytes releasing a multiplicity of factors in the form of diverse adipokines, as well as fatty acids and other lipid moieties (Frühbeck et al, 2001;Trayhurn & Beattie, 2001;Rajala et al, 2003;Trayhurn, 2013). A number of adipokines are associated with the immune system and inflammation, and the expression and secretion of some of these protein signals and factors rise in obesity (Rajala et al, 2003;Hotamisligil, 2006;Trayhurn, 2013); examples include TNFα (tumour necrosis factor α), IL-6 (interleukin-6) and leptin. A notable exception is the hormone adiponectin, with its anti-inflammatory and insulin sensitising actions (Ouchi et al, 1999;Yokota et al, 2000;Berg et al, 2001;Yamauchi et al, 2001), the production and secretion of which falls as fat mass expands (Arita et al, 1999;Hotta et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…White adipocytes secrete a number of adipokines that affect eating behaviour (leptin) (20) and metabolism (e.g. adiponectin, resistin, adipsin) (21). Brown adipocytes also secrete hormones and growth factors (e.g.…”
mentioning
confidence: 99%
“…Thus, one of the mechanisms triggering inflammation has been associated with adipose tissue hypoxia [4] or increased oxygen tension [5], which affect a number of genes such as HIF-1a, MCP-1, IL-6, GLUT-1, ANGPTL-4 and PPAR-γ [6] that could be involved as a cause or as a consequence reaction to pathologically low or high oxygen conditions. Interestingly, as we hypothesized previously [3] and Kong et al have nicely demonstrated in their article [1], hypoxia is not only an ethological factor or a manifestation of disease, but also a therapeutic tool following different patterns (hypoxic exposure, hypoxic training, intermittent hypoxia under hyperbaric and normobaric conditions), which has been used for pre-acclimation in climbers, or to improve athletes performance as well as for heart, respiratory and nervous system diseases or to regulate body weight [7].…”
mentioning
confidence: 99%